Meningkatkan Kedisiplinan Siswa melalui Layanan Bimbingan Klasikal Masa Covid-19 pada Siswa Kelas IX.A SMPN 3 Masbagik - Hamdan, Hamdan (MASALIQ, 2021)
This counseling guidance class action research aims to determine the effectiveness of Classical Services in Improving Discipline of Class IX-A Students of SMPN 3 Masbagik for the 2020/2021 Academic Year during the covid-19 pandemic. By using classical guidance services, it focuses on providing maximum assistance so that the final hope can increase the level of student discipline in participating in learning activities in all subjects studied for a week. in the first cycle it was obtained by 62% and in the second cycle the student discipline level was obtained by 100%, meaning there was an increase from the first cycle to the second cycle. Thus, classroom action research on counseling counseling by applying this classical guidance service can be said to be very effective in improving student discipline in the learning process.